تجليات الحداثة في الخطاب الشعري العربي مطلع الألفية الثالثة - مقاربة تأويلية - - محمـــــــد جلابي (University of M'Sila, 2025)
أدت التحولات السياسية في الوطن العربي إلى إيقاظ العديد من الإشكاليات، فوضعتها في دائرة الضوء بعد أن كانت منصهرة داخل تكتلات سياسية وثقافية خاضعة لسلطة الحاكم، على غرار مسألة الهوية التي طفت إلى السطح محدثة شروخا كبيرة، أفرزت تكتلات تستند إما إلى العصبيات العرقية أو إلى الطائفيات والمذهبيات الدينية، وكنتيجة حتمية لهذا التفكك تعددت الخطابات وتصادمت فيما بينها رغبة في تحصين الذات وحمايتها من الآخر، في ظل تراجع الشعارات الكبرى كالوحدة والحرية. كل ذلك كان له الأثر في الخطابات المهيمنة في بعدها السياسي، إضافة إلى البعدين الثقافي والفكري،حيث انتقلت القوة من المركز المسيطر إلى الفئات البسيطة المهمشة التي لم تعد تقبل بمن يعبر عن همومها وانشغالاتها إلا إذا كان منخرطا معها في واقعها ويعيش معها آلامها و آمالها، رافضة خطاب الخضوع والإخضاع الذي تبنته النخب المثقفة في التعبير عن مصالح الطبقة السياسية و فرض رؤيتها كوضع طبيعي،وبالتالي اعتبرت هذه النخب امتدادا للأنظمة الفاسدةوجب إزاحتها وإبعادها من المشهد كشكل من أشكال الثورة، و هذا ما يقع في صميم اهتمامات نظرية الخطاب التي لا تدرس الخطاب نفسه، بل تركز على العناصر و الكيفيات التي ينشأ عنها الخطاب، و بها يحقق هدفه وتأثيره. من هذه المنطلقات نسعى من خلال بحثنا إلى رصد تمثلات الحدث الثوري في الخطابات الشعرية التي أفرزتها التحولات السياسية مطلع الألفية الثالثة، من خلال الإجابة عن عديد من التساؤلات: ما هي منطلقات الحداثة الشعرية و هل كانت مشحونة بشحنات إيديولوجية؟ أم كانت متحررة من كل ما من شأنه أن يجعلها خاضعة لنسق من المعايير والقيم سواء السياسية أو الدينية؟ كيف نظر الشعراء الرواد إلى هذه التحولات؟ وكيف أسسوا من خلالها رؤيتهم الشعرية الحديثة؟ ما موقف المرأة الشاعرة من هذا الحراك؟ وما هي إسهاماتها في تحديث الشعر العربي؟
The political transformations in the Arab world have brought many issues to light, exposing them after they had previously been dissolved within political and cultural blocs under the authority of the ruler. One of these issues is identity, which reemerged, and caused significant internal fractures and provoked smaller factions based on ethnic loyalties, tribal sectarianism, and religious doctrines. As an inevitable consequence of this fragmentation, multiple discourses emerged, clashing with one another and everyone in this conflict is trying to protect and fortify their own identities against the "other," especially considering the decline of big slogans such as "unity" and "freedom". These changes had a profound impact on dominant discourses, particularly in their political and cultural dimensions. Amid this intellectual congestion, power shifted from the central authority to marginalized groups, who no longer accepted any form of representation unless it came from those who shared with them their own lived reality, struggles, hopes, and pains. These groups rejected the discourse of submission and subjugation adopted by intellectual elites, who had traditionally worked to express and defend the interests of the political class and imposed their vision as the natural order. The result was that, these elites were seen as an extension of corrupt regimes and their removal from the scene was regarded necessary as a form of revolution. This dynamic lies at the heart of discourse theory, which does not merely study discourse itself but rather focuses on the elements and mechanisms that shape discourse, enabling it to achieve its goals and influence its audience. Starting from these premises, our research aims to examine the manifestations of the revolutionary state in the poetic discourses that emerged from the political transformations of the early 21st century by answering questions such as: What are the foundations of poetic modernism, and was it ideologically charged? Or was it free from any constraints that would subject it to political pressure or religious values? How did pioneering poets perceive these transformations? And how did they shape their poetic vision in response? Were poets able to transform the revolutionary movements in the streets into a real poetic revolution that reflected a different perspective and a new formulation of the newly born norms? Or were these changes too sudden to allow poets the opportunity to develop a modern poetic vision? Additionally, what was the standpoint of female poets toward this movement? What were their contributions to the modernization of Arabic poetry?
Keywords: الحداثة الشعرية،نظرية الخطاب، الهوية ، الرؤية الشعرية ، الفئات المهمشة; Poetic modernism.; Discourse theory; .Identity.; Poetic vision; Marginalized groups